2016
DOI: 10.1098/rspb.2016.0687
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of eggshell cuticle in relation to nesting ecology

Abstract: Avian eggs are at risk of microbial infection prior to and during incubation. A large number of defence mechanisms have evolved in response to the severe costs imposed by these infections. The eggshell's cuticle is an important component of antimicrobial defence, and its role in preventing contamination by microorganisms in domestic chickens is well known. Nanometer-scale cuticular spheres that reduce microbial attachment and penetration have recently been identified on eggs of several wild avian species. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 65 publications
0
65
0
1
Order By: Relevance
“…Such factors could include natural and nest‐specific humidity, nest material composition, and environmental and nest‐specific temperatures. All of these could affect the intrinsic growth of bacteria on eggshells, the effectiveness of antimicrobial defenses, and, ultimately, embryonic viability due to trans‐shell infections (Brandl et al., 2014; Cook et al., 2003; D'Alba et al., 2016; Ruiz‐Castellano, Tomás, Ruiz‐Rodríguez, Martín‐Gálvez, & Soler, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such factors could include natural and nest‐specific humidity, nest material composition, and environmental and nest‐specific temperatures. All of these could affect the intrinsic growth of bacteria on eggshells, the effectiveness of antimicrobial defenses, and, ultimately, embryonic viability due to trans‐shell infections (Brandl et al., 2014; Cook et al., 2003; D'Alba et al., 2016; Ruiz‐Castellano, Tomás, Ruiz‐Rodríguez, Martín‐Gálvez, & Soler, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In birds, which are exclusively oviparous, the eggshell surface and calcium carbonate matrix are host to a diverse bacterial fauna (Baggott & Graeme-Cook, 2002;Grizard, Dini-Andreote, Tieleman, & Salles, 2014;Kobayashi, Gutierrez, & Hatta, 1996), and trans-shell penetration by some microbes can be lethal to the developing embryo (Cook, Beissinger, Toranzos, Rodriguez, & Arendt, 2005;Godard, Morgan Wilson, Frick, Siegel, & Bowers, 2007). Consequently, diverse antimicrobial barriers and defenses have evolved on and within the avian egg (D'Alba, Maia, Hauber, & Shawkey, 2016;D'alba & Shawkey, 2015). Those defenses that are interior to the egg include lysozyme, ovotransferrin, and other antimicrobial proteins in the albumen and the vitelline membrane (Guyot et al, 2016;Wellman-Labadie, Picman, & Hincke, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a subsequent study found that cuticular nanospheres occur most commonly on the eggs of species that nest in warm, humid environments, suggesting an antimicrobial function (D'Alba et al . ). These nanospheres are most commonly formed of hydroxyapatite or other forms of calcium phosphate (D'Alba et al .…”
Section: Discussionmentioning
confidence: 97%
“…These nanospheres are most commonly formed of hydroxyapatite or other forms of calcium phosphate (D'Alba et al . ), but vaterite may play a similar role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation